Diadenosine tetraphosphate-induced inhibition of ATP-sensitive K+ channels in patches excised from ventricular myocytes. - Jovanovic, A. (1996)
Diadenosine 5',5''-P1,P4-tetraphosphate (Ap4A) has been termed 'alarmone' due to its role in intracellular signaling during metabolic stress. It is not known whether Ap4A could modulate ATP-sensitive K+ (KATP) channels, a family of channels regulated by the metabolic status of a cell. We applied the single-channel patch-clamp technique to measure the effect of Ap4A on KATP channels. When applied to the intracellular side of patches, excised from guinea-pig ventricular myocytes, Ap4A inhibited KATP channel activity, in a reversible and concentration-dependent (half-maximal concentration approximately 17 microM) manner. We conclude that Ap4A, a naturally occurring diadenosine polyphosphate, is actually an inhibitor of the myocardial KATP channel.